Psycholinguistic Aspects of the Development of Students’ Critical Approach to the Solution of Terminological Problems in Online Translation Learning - Chernovaty, Leonid; Kovalchuk, Natalia (East European Journal of Psycholinguistics, 2021)
The research is aimed at exploring the approaches to increase the efficiency of the development of the future translators’ critical approach to the solution of terminological problems, as well as the specialized bilingual (English and Ukrainian) terminology acquisition, in online teaching and learning. The method of research is based on the assumption that the said increase can be achieved through the intensification of the students’ analytical and thinking activity in their independent work by means of post-editing the machine-translated target texts combined with the simultaneous written explanation of the reasons for the respective corrections. This assumption was tested in the pilot experimental online teaching of specialised (in the domain of Psychology) translation to the first-year MA students majoring in Translation. The participants’ performance assessment took into account the amount of the independent work done by them, the level of their critical approach, as well as the specialised terminology usage accuracy in the final translation test. The results of the analysis proved the apparent dependence of the participants’ critical approach to the solution of terminological problems and the efficiency of specialised terminology acquisition on the intensity of their analytical and thinking activity in their independent work. The advantage of the participants with the highest level of the said intensity over those with the average one amounted to 16%, and 40% – over those with the lowest intensity. The efficiency of the development of students’ critical approach to the solution of terminological problems and the specialised terminology acquisition in online translation teaching and learning may be increased by intensification of their analytical and thinking activity in the process of meaningful post-editing of machine-translated target texts.